Stefan Swieżawski and Ancient Philosophy - Nerczuk, Zbigniew (Roczniki Filozoficzne, 2025)
Although the main subject of Stefan Swieżawski’s research was medieval philosophy, ancient philosophy played an essential role in his thought. In its first part, the article discusses his classical education and interest in the philosophy of Plato and Aristotle, which was born during his philosophical studies at Jan Kazimierz University in Lviv. In the second part, the article presents the approach to ancient philosophy included in the monograph Dzieje europejskiej filozofii klasycznej, published in 2000, which starts with the history of ancient philosophy. This section of the article discusses the creation of the monograph, which emerged from Swieżawski’s lecture notes, as well as the methodological basis of the work, the topics discussed, the secondary literature used, and his approach to ancient philosophy.